Humoral Immunity of Broilers is Affected by Oil Extracted Propolis (OEP) in the Diet - Taheri, H.R.; Rahmani, H.R.; Pourreza, J. (International Journal of Poultry Science, 2005)
This study was conducted to determine the effect of different levels of oil extracted propolis (OEP) on humoral immunity of broilers from 1st to 7th week of age. The experiment started with 672 chicken (Ross 308, 336 marked male and female), in a completely randomized design test with 7 treatments, 4 replicates and 24 chicken (12 male, 12 female) per treatment. Chicken received the normal soybean meal-corn diet supplemented with 0 (control), 40, 70, 100, 400, 700 and 1000 mg/kg of OEP. Immunization program included vaccination against infectious bronchitis virus (IB, H120 on days one and 8 spray; H52 on day 30 drinking), Newcastle disease (ND, B1, day 10, eye drop; Lasota days 20 and 32 drinking) and infectious bursal disease (BD, or Gumboro, D78, days 12 and 24, eye drop). Blood samples were collected two times on days 21 and 42 of age, via brachial vein from one male and one female of each replicate and plasma was separated by centrifugation. Antibody concentration against IB, ND, BD and avian influenza (AI) were measured by ELISA method. Results indicated that antibody titer against AI, ND and BD were significantly (P<0.05) increased with OEP supplementation, without any effect on IB. Relatively negative effect of higher concentration of OEP on humoral immunity of broilers, concluded that broiler`s immune system may respond to OEP on a crucial dosage.